The judicial review of constitutionality in Argentina - Ylarri, Juan Santiago (Derecho Público Iberoamericano, 2019)
The purpose of this paper is to analyze judicial review in Argentina. The organization of the Judicial Power, in particular the procedure of appointment and removal of the judges of the Supreme Court and lower federal courts will be studied. The characteristics of judicial review system in Argentina will be developed, as well as the case or controversy requirement, the declaration of unconstitutionality ex officio by Courts, and the debate on whether precedents of the Supreme Court are mandatory. Also, the Supreme Court’s original and appellate jurisdiction will be analyzed. Finally, reference will be made to two mechanisms recently introduced by the Supreme Court that helps legitimize the performance of the Judiciary.